Design of the Social Media Marketing Strategy Model for Temanggung SME Products in the Covid-19 Pandemic Era - Sandi - Supaya; Yusmar Ardhi Hidayat; Mardinawati - Mardinawati (Politeknik Negeri Semarang, 2023)
The problems in this study focused on identifying target markets, platforms and social media content, as well as designing social media marketing strategy models for Temanggung UKM products in the Covid-19 Pandemic Era. Questionnaire data in this study includes target markets, platforms, content, and social media marketing strategies. The social media marketing strategy questionnaire consists of questionnaires relating to when customers search for the type of content, reasons customers consume, how customers consume content, social media celebrities who are close to customers, and the response of SMEs when there are customer complaints. From this study it was concluded that the target market for UKM Temanggung consists of teachers, housewives, and students. The social media platforms used are WhatsApp, Facebook, Instagram with new product introduction content, interesting stories or inspiration related to the products being sold, product promotions being sold, tutorials using the products being sold accompanied by subtle promotions. Content is delivered on weekends via podcasts and vedio. Customers are close to social media and local artists, Temanggung ambassadors, service people, endorse friends, relatives. Every complaint is handled properly by Temanggung SMEs.